2022
DOI: 10.3390/rs14051063
|View full text |Cite
|
Sign up to set email alerts
|

Combining Spectral and Textural Information from UAV RGB Images for Leaf Area Index Monitoring in Kiwifruit Orchard

Abstract: The use of a fast and accurate unmanned aerial vehicle (UAV) digital camera platform to estimate leaf area index (LAI) of kiwifruit orchard is of great significance for growth, yield estimation, and field management. LAI, as an ideal parameter for estimating vegetation growth, plays a significant role in reflecting crop physiological process and ecosystem function. At present, LAI estimation mainly focuses on winter wheat, corn, soybean, and other food crops; in addition, LAI on forest research is also predomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 64 publications
3
16
0
Order By: Relevance
“…Zha et al (2020) also found that RF was superior to SVR, MLR and ANN in predicting nitrogen content in rice using spectral features. These conclusions are consistent with previous prediction studies of other crops traits (Lee et al, 2020;Zhang et al, 2022c). The RF model, which is a popular ensemble learning algorithm, utilizes bootstrap resampling to extract multiple sample sets from the original sample, forming sample subsets.…”
Section: Estimation Of Lai and Lcc By Fusion Of Preparation Indices A...supporting
confidence: 93%
See 1 more Smart Citation
“…Zha et al (2020) also found that RF was superior to SVR, MLR and ANN in predicting nitrogen content in rice using spectral features. These conclusions are consistent with previous prediction studies of other crops traits (Lee et al, 2020;Zhang et al, 2022c). The RF model, which is a popular ensemble learning algorithm, utilizes bootstrap resampling to extract multiple sample sets from the original sample, forming sample subsets.…”
Section: Estimation Of Lai and Lcc By Fusion Of Preparation Indices A...supporting
confidence: 93%
“…In assessing aboveground biomass (AGB) in winter oilseed rape fields, Liu et al (Liu et al, 2019) found single texture indices less accurate than vegetation indices (VIs). Machine learning algorithms have been demonstrated to possess robust capabilities for handling non-linear and multivariate regression between remote sensing data and vegetation physiological and biochemical parameters (Ma et al, 2022;Zhang et al, 2022c). The RF model performed better than the SVR model in the three machine learning models, while the BP model was the weakest in all three types of data inputs.…”
Section: Estimation Of Lai and Lcc By Fusion Of Preparation Indices A...mentioning
confidence: 99%
“…Yu et al [88] used both multivariate and univariate algorithms to construct prediction models of LAI, and found that the multivariate models outperformed the univariate models in estimating LAI in a forest. Similar results were also found in the studies of LAI in wheat [75,76], kiwifruit orchard [89] and soybean in this study. The possible reason for this might be that multivariate algorithms can include more variables with explanatory power and can reduce the possibility of omitting variable bias.…”
Section: Comparison Of Prediction Models Of Lai Based On Different Al...supporting
confidence: 92%
“…Furthermore, as rice is a row-cropped crop with an apparent spatial direction, the directional selection may impinge upon the monitoring performance of TFs in assessing AGB. However, previous studies have primarily relied on default texture parameters setting (such as a 3x3 window size and diagonal direction at 45°) ( Zheng et al., 2018 ; Li et al., 2019 ; Zheng et al., 2019 ; Xu L. et al., 2022 ; Zhang D. et al., 2022 ; Zhang Y. et al., 2022 ;) or a directionless approach (by averaging multiple directional TFs to eliminate the directional effect) ( Wang F. et al., 2021 ; Liu et al., 2022a ; Xu T. et al., 2022 ) when extracting GLCM-based TFs. A quantitative analysis of the impact of TFs derived from different window sizes and direction parameters for crop AGB estimation has been omitted from these studies.…”
Section: Introductionmentioning
confidence: 99%